(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Nanotechnology has fundamentally transformed the landscape of pharmaceutical sciences, offering unprecedented control over how therapeutic agents reach their intended targets within the human body. Conventional drug delivery methods frequently suffer from poor bioavailability, rapid systemic clearance, and non-specific distribution, leading to suboptimal therapeutic outcomes and dose-limiting toxicities. This article examines the evolution, mechanisms, and clinical impact of nanotechnology-based drug delivery systems (NDDS). By exploring major nanocarrier classes—including lipid-based nanoparticles, polymeric systems, dendrimers, and inorganic nanomaterials—this review illustrates how engineered nanoscale platforms enable passive and active targeting, stimuli-responsive release, and combination therapies. The discussion further addresses current translational challenges, including regulatory hurdles, manufacturing scalability, and long-term safety profiles. As nanomedicine continues to mature, its integration with artificial intelligence and personalized medicine approaches promises to redefine therapeutic paradigms across oncology, neurology, infectious diseases, and beyond.